Negotiating Gender and Tradition: Female Agency and Familial Transformation in Anita Rau Badami’s the Hero’s Walk - Dr. Jagbir Singh (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The paper is based on the questions of gender and family which are discussed in The Heroes Walk by Anita Rau Badami. Born in India, but living in Canada, Badami combines her multi-ethnic background and current setting to create a novel that explores the complexity of modern living among the fictional family of Indian Brahmans in the small town of Toturpuram. The case of Sripathi Rao, his wife Nirmala and his daughter Maya gives us an insight into the changing roles of women in the family. The marriage of an Indian girl Maya and a white man in Vancouver brings conflict to the family. We can see how tragedy affects the relationships within the family, cultural norms and traditional beliefs through the eyes of Sripathi Rao. The character of Nirmala is a symbol of the empowerment and independence of modern women. Arranging a marriage between her brother and sister-in-law, settling the family, and bringing up her granddaughter Nandana are all examples of how a modern lady can go against the grain. The book is about women and how they can become a force of change in their family and community and how women can be a bridge between tradition and modernity. In its most basic form, The Hero’s Walk is a tale of the significance of understanding, compassion, and unity against all odds, and the connections that can be established inside a family. This discussion is based on a wide range of academic sources and reviews to explore in-depth the themes and character development of the novel and demonstrates that it has significance in both postcolonial literature and gender studies.